Platelet-Rich Plasma and Adipose-Derived Mesenchymal Stem Cells in Association with Arthroscopic Microfracture of Knee Articular Cartilage Defects: A Pilot Randomized Controlled Trial. (28th April 2022) - Venosa, Michele; Calafiore, Francesco; Mazzoleni, Manuel; Romanini, Emilio; Cerciello, Simone; Calvisi, Vittorio
Abstract : Background . This study aims to compare the effects of platelet-rich plasma (PRP) alone or in combination with adipose-derived mesenchymal stem cells (AD-MSCs) in patients affected by cartilage defects, undergoing knee arthroscopic microfracture. Methods . Thirty-eight patients diagnosed with a knee monocompartmental cartilage defect (Outerbridge grade IV) on the MRI, underwent an arthroscopic procedure. After the confirmation of the lesion, they all received the same bone marrow stimulation technique (microfracture) and were randomized into two groups: the first one had additional PRP injection (group A), while the second received PRP and AD-MSC injection (group B). Knee assessment and pain score were documented with Knee Injury Osteoarthritis Outcome Score (KOOS), International Knee Documentation Committee (IKDC) score, Short-Form (SF) 12, and Visual Analogue Scale (VAS) before the treatment and at 1, 3, 6, and 12 months of follow-up postoperatively. An additional arthroscopic procedure, performed in four patients for a subsequent meniscal lesion, let us evaluate cartilage evolution by performing a macro/microscopical assessment on cartilage biopsy specimens. Results . At the 12-month follow-up, both groups showed a comparable functional improvement. The scores on the IKDC form, KOOS, pain VAS, and SF-12 significantly improved from baseline (p < 0.05 ) to 12 months postoperatively in both treatment groups. The four second-look arthroscopies showed a complete repair of the articular defects by smooth solid cartilage layer, with a good chondrocytic population, in both groups. A thick smooth hyaline-like cartilage with a predominantly viable cell population and normal mineralization (a form closely resembling native tissue) was observed in group B. Conclusions Modern regenerative medicine techniques, such as PRP and AD-MSC, associated with traditional arthroscopic bone marrow stimulating techniques, seem to enhance cartilage restoration ability. The preliminary results of this pilot study encourage the synergic use of these regenerative modulating systems to improve the quality of the regenerated cartilage.